PENGUATAN PEMBERDAYAAN MASYARAKAT MELALUI INOVASI PENGELOLAAN SAMPAH DENGAN TEBA MODERN DI BANJAR BELALUAN DESA SINGAPADU TENGAH - Pande Wayan Pajar Kencana; Ni Komang Ayu Sawitri Dewi; Ni Made Ayu Mega Mustika; Dicky Dewanta; Maria Selasi Namung; Ni Luh Putu Indrawathi (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2026)
This activity aims to strengthen the empowerment of the Banjar Belaluan community, Singapadu Tengah Village, Sukawati District, in integrated waste management based on organic waste sorting and Modern Teba innovation. The main problem in Banjar Belaluan, Singapadu Tengah Village is the low public awareness in sorting and processing waste from its source and the still limited sustainable management system. To address this, the activity was carried out with a qualitative descriptive approach using the Participatory Action Learning System (PALS) method which emphasizes active community involvement at every stage, from socialization, training, to the implementation of Modern Teba. Data were collected through observation and documentation to determine changes in behavior, participation levels, and activity effectiveness. The results of the implementation showed an increase in public awareness in sorting organic waste from the source, where most people have separated organic, inorganic, and residual waste independently. Organic waste is processed into compost with the Modern Teba system located in the temple area as a place for Modern Teba innovation for organic waste processing in the temple area. Furthermore, this program aims to raise community awareness in their daily activities at home and in the surrounding environment regarding organic waste processing and waste sorting. In addition to promoting environmentally friendly behavior, this program also encourages the formation of local institutions that coordinate waste management activities at the village level. Overall, this activity demonstrates that participatory community empowerment is effective in creating an independent, sustainable waste management system and supporting the green development vision of Nangun Sat Kerthi Loka Bali.